Organicity in contemporary ceramics - Saad Hafid Obaid (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
This study examines organicity in contemporary ceramics, focusing on the aesthetic use of organic forms as sources of visual, symbolic, and expressive meaning. The research problem arises from the transformation of form in contemporary ceramic art, moving from the imitation of nature toward abstraction, stylization, and conceptual reinterpretation. The study aims to identify and analyze how organic forms, derived from the human body, animals, and natural elements, are represented in contemporary ceramic works. The research adopts a descriptive-analytical method, using a purposive sample of three ceramic works that demonstrate organic characteristics. The analysis is based on formal elements such as shape, color, texture, line, movement, the relationship between the artwork and its surrounding space, and the symbolic meanings produced by its visual structure. The findings reveal that organic forms in contemporary ceramics do not merely function as representations of nature but also serve as aesthetic transformations capable of generating expressive, symbolic, and intellectual values. Organicity in ceramic works demonstrates formal flexibility, visual dynamism, and the ability to create a meaningful relationship between natural reality, the artist’s imagination, and the viewer’s experience. The study concludes that the use of organic forms plays a significant role in expanding the visual language of contemporary ceramics, shifting it from traditional functional forms toward modern artistic expression that is reflective, interpretive, and open to multiple readings.